Consentius’ De barbarismis et metaplasmis (Circe de clásicos y modernos, 2018)
Consentius lived in Gaul in the fifth century, and he was the author of a grammatical work, parts of which are now preserved as de duabus partibus orationis nomine et uerbo (GL5.338-385) and de barbarismis et metaplas-mis (GL 5.386-404). The latter is the largest discourse on barbarisms written by the Romans, and its importance for the classical studies derives from the fact that, with the exception of the Appendix Probi, it is the only work that provides numerous examples of the pronuncia-tion of the spoken language. It also offers an overview of the state of the language along with examples of dialectal peculiarities, as well as of grammatical studies in relation to the time it was composed. The translation presented here is the first complete translation of the ars de barbaris-mis et metaplasmis to a modern language.
Keywords: Consentius; Ars grammatica; Grammatici latini; barbarisms; metaplasms